Self-Expandable Stent-Assisted Coiling of Wide-Necked Intracranial Aneurysms: A Single-Center Experience - Akpek, Sergin; Arat, Anil; Morsi, Hesham; Klucznick, Richard P.; Strother, Charles M.; Mawad, Michel E. (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: Endovascular treatment of wide-necked aneurysms remains a therapeutic challenge. We conducted this study to evaluate the angiographic results and clinical outcome of patients treated with stent-assisted coiling by using a recently available self-expandable intracranial stent.METHODS: A retrospective review of all patients treated with self-expandable stent-assisted coiling between September 2002 and December 2003 was done. Treatment was attempted in 32 patients with 35 aneurysms. Four of the aneurysms were ruptured. All had either a dome-to-neck ratio less than 2 and/or a neck diameter of 5 mm or larger. Following stent placement, coiling was attempted in 33 of 34 aneurysms. The technical success of the procedure, procedure related complications, and the angiographic results were documented.RESULTS: In 34 of 35 aneurysms, stent deployment across the neck of the aneurysm was successful. Coiling was performed successfully in 30 of 33 aneurysms. In 20 aneurysms, immediate posttreatment angiography showed either total (17%) or satisfactory (50%) occlusion. Procedure-related mortality occurred in one patient (3.1%). Adverse events occurred in eight patients (25%); in three of them permanent neurologic deficit resulted (9.3%). In six patients, thrombus formation occurred within the stented segments during the procedure and reopro infusion was used. Follow-up angiography was available in 12 (40%) of 30 treated aneurysms.CONCLUSION: In our practice use of the self-expandable stent seemed to facilitate endovascular treatment of wide-necked intracranial aneurysms. Difficulty of deployment and stent thrombogenicity are the main drawbacks of the system.